Ultimate limits of reinforced concrete hinges. (1st December 2020) - Schlappal, Thomas; Kalliauer, Johannes; Vill, Markus; Mang, Herbert A.; Eberhardsteiner, Josef; Pichler, Bernhard L.A.
Highlights: Analytical formulae for verification of ultimate limits are derived. Rebars crossing the neck of reinforced concrete hinges are accounted for. Cracking beyond half of the width of the neck is accepted because of the rebars. The usefulness of the formulae is demonstrated based on experimental data. Eurocode-compatible design recommendations are elaborated and exemplarily applied. Abstract: This work is a further development of its predecessor, the topic of which was verification of serviceability limit states of reinforced concrete hinges. Herein, the same conceptual approach is used to derive analytical formulae, supporting verification of ultimate limit states. These formulae limit tolerable relative rotations as a function of the compressie normal force transmitted across the neck. The mechanical model is based on the Bernoulli-Euler hypothesis and on linear-elastic and ideally-plastic stress-strain relationships for both concrete in compression and steel in tension. The usefulness of the derived formulae and the corresponding dimensionless design diagrams is assessed by means of experimental data from structural testing of reinforced concrete hinges, taken from the literature. This way, it is shown that the proposed mechanical model is suitable for describing ultimate limit states. Corresponding design recommendations are elaborated and exemplarily applied to verification of ultimate limit states of the reinforced concrete hinges of a recently built integral bridge. Since the reinforcement is explicitly accounted for, the tolerable relative rotations are larger than those according to existing guidelines. It is included that bending-induced tensile macrocracking beyond one half of the smallest cross-section of the neck is acceptable, because the tensile forces carried by the reinforcement ensure the required position stability of the hinges.